2005
DOI: 10.1002/jmr.720
|View full text |Cite
|
Sign up to set email alerts
|

Selective recognition of neodymium (III) using ion imprinted polymer particles

Abstract: Neodymium (III) ion-imprinted polymer (IIP) materials were prepared by the copolymerization of neodymium (III)-5,7-dichloroquinoline-8-ol-4-vinylpyridine ternary complex with styrene(monomer), divinyl benzene (crosslinking monomer) in the presence of 2,2'-azobisisobutyronitrile (initiator). The synthesis was carried out in 2-methoxy ethanol medium (porogen) and the resultant material was filtered, washed, dried and powdered to form unleached IIP particles. The imprint ion was removed by stirring the above part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…The same authors reported a 2 -4-fold enhancement in selectivity coefficients by post-c-irradiation of dysprosium(III) IIP particles [10]. Selective recognition of neodymium(III) from La, Ce, Pr, Sm and Eu was achieved by using neodymium(III) IIP particles [11]. Kala et al [12 -14] reported higher selectivity coefficients for erbium over Y, Dy, Ho, Tb and Tm by employing erbium(III) IIP particles prepared by thermal, photochemical and c-irradiation polymerization methods over nonimprinted polymer particles.…”
Section: Introductionmentioning
confidence: 91%
“…The same authors reported a 2 -4-fold enhancement in selectivity coefficients by post-c-irradiation of dysprosium(III) IIP particles [10]. Selective recognition of neodymium(III) from La, Ce, Pr, Sm and Eu was achieved by using neodymium(III) IIP particles [11]. Kala et al [12 -14] reported higher selectivity coefficients for erbium over Y, Dy, Ho, Tb and Tm by employing erbium(III) IIP particles prepared by thermal, photochemical and c-irradiation polymerization methods over nonimprinted polymer particles.…”
Section: Introductionmentioning
confidence: 91%
“…More particularly in the case of ionic imprinting, the affinity partly depends on the number and the orientation of interaction points (ligand denticity) as well as on the counter ion. As described in the paper by (Krishna et al (2005) ion imprinting allows significant enhancement in selectivity coefficients of neodymium(III) with respect to La(III), Ce(III), Pr(III), Sm(III) and Eu(III). The obtained selectivity coefficients are several times higher than those for the best extractant such as D2EHPA, for example selectivity coefficient for Nd(III) over Ce(III) and Pr(III) increases twentyfold, threefold over La(III) and Sm(III).…”
Section: Separation Using Chelating Ion Exchangersmentioning
confidence: 97%
“…They synthesized IIP particles via a single pot reaction for separation of Y(III) from selected lanthanides, 233 and Er(III) IIP particles via thermally copolymerizing 234 and photochemical polymerization, 235 respectively. What's more, Nd(III) IIP materials 236 were prepared as well and also had good results. Guo et al 237 prepared Nd(III)-IIPs followed by ICP-AES determination with the largest selectivity coefficient, over 110, for Nd(III) in the presence of competitive ions such as La(III), Ce(III), Pr(III) and Sm(III).…”
Section: Rare Earth Elements Iipsmentioning
confidence: 99%